FAT SOLUBLE VITAMIN DEFICIENCY IN CHILDREN WITH CYSTIC FIBROSIS IN NSW. (February 2015) - Rana, Malay; Wong-See, Denise; Katz, Tamarah; Gaskin, Kevin; Whitehead, Bruce; Jaffe, Adam; Coakley, John; Lochhead, Alistair
Abstract : Aims: To evaluate fat-soluble vitamin status and prothrombin time (PT) in children with cystic fibrosis (CF) aged ⩽18 years in NSW and to assess rates of deficiency from 2007–2010. Methods: A retrospective analysis of fat-soluble vitamin levels and PT in children aged ⩽18 years who lived in NSW and attended any of the three paediatric CF centres from 2007–2010. An audit of demographic and clinical data during the first vitamin level measurement of the study period was performed. Results: Deficiency of one or more fat-soluble vitamins was present in 240/530 children (45%) on their first vitamin test in the study period. The prevalence of vitamin D and E deficiency fell from 22.11% to 15.54% and 20.22% to 13.89%, respectively, from 2007–2010. The prevalence of vitamin A deficiency increased from 11.17% to 13.13%. Vitamin K was measured infrequently. Prolonged PT was common. Low vitamin levels were associated with poor clinical status. Discussion: This is one of few studies of fat-soluble vitamin deficiency in children with CF in Australia. Testing of vitamin K-dependant factors needs consideration. Further studies are needed to continue monitoring rates of vitamin deficiency in the CF community.